Impact of the 138,139La radiative strength functions and nuclear level densities on the galactic production of 138La - Kheswa, Bonginkosi Vincent (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.